Visible-Light Photoinitiating Systems for Laser Imaging Using Pyrromethene Dyes - Ibrahim, Ahmad (2012)
In this paper, a new three-component photoinitiating system based on pyrromethene dyes was shown to exhibit high performance for laser imaging at 532 nm. Pyrromethene dye was used with a reductant coinitiator (Amine) and oxidant coinitiator (Triazine). The initial mechanism of reaction depends on the relative concentration of the oxidant and the reductant. After reaction between the excited dye and the coinitiator, secondary reactions involving the second redox additive take place, leading to beneficial effects such as dye ground state recovery and formation of additional initiating species. The efficiency of these processes is deeply investigated, and the effect on the polymeric network formation is detailed.